Plasmon-activated water effectively relieves hepatic oxidative damage resulting from chronic sleep deprivation. Issue 18 (5th March 2018) - Chen, Hsiao-Chien; Cheng, Chung-Yi; Chen, Li-You; Chang, Chun-Chao; Yang, Chih-Ping; Mai, Fu-Der; Liao, Wen-Chieh; Chang, Hung-Ming; Liu, Yu-Chuan
Abstract : Intrinsic anti-oxidative activity of PAW protects the liver from CSD-induced oxidative damage. Abstract : The role of the hepato-protective agent plasmon-activated water (PAW) as an innovative anti-oxidant during chronic sleep deprivation (SD) is realized in this study. PAW possesses reduced hydrogen-bonded structure, higher chemical potential and significant anti-oxidative properties. In vitro tests using rat liver cell line (Clone-9) have demonstrated that PAW is non-cytotoxic and does not change the cellular migration capacity. The in vivo experiment on SD rats suffering from intense oxidative damage to the liver, an extremely common phenomenon in the present-time with deleterious effects on metabolic function, is performed by feeding PAW to replace deionized (DI) water. Experimental results indicate that PAW markedly reduces oxidative stress with enhanced bioenergetics in hepatocytes. PAW also effectively restores hepatocytic trans -membrane ion homeostasis, preserves membranous structures, and successfully improves liver function and metabolic activity. In addition, the hepato-protective effects of PAW are evidently demonstrated by the reduced values of glutamic oxaloacetic transaminase (GOT) and glutamic pyruvic transaminase (GPT) and the recovery of total protein and albumin levels. With clear evidences of PAW for protecting liver from SD-induced injury, delivering PAW as a powerful hepato-protective agent should be worthy of trailblazing new clinical trials in a healthier, more natural, and more convenient way.